Volume 2B: Turbomachinery 2019
DOI: 10.1115/gt2019-90476
|View full text |Cite
|
Sign up to set email alerts
|

LDV Characterization of Unsteady Vaned Diffuser Flow in a Centrifugal Compressor

Abstract: Modern turbomachinery faces increased performance demands in terms of efficiency, compactness, and pressure-rise. Advancements in computational technology have allowed numerical methods to become the backbone of design development efforts. However, the unique complexities of centrifugal compressor flow-fields pose difficult computational problems. As such, advanced experimental methods must be used to obtain high-quality datasets to further inform, improve, and validate computational methods in complex flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, unsteadiness is one such flow driver that can significantly impact the measured flow field. Recent experimental measurements of the unsteady velocity field through the diffuser show that unsteadiness persists further into the diffuser passage than typically assumed [21], suggesting a strong influence of unsteady effects on the flow field. The methodology used for model selection herealways stepping towards a more physically realistic modelwas done to minimize the impact of omitted flow drivers.…”
Section: Frozen Rotor Resultsmentioning
confidence: 95%
“…However, unsteadiness is one such flow driver that can significantly impact the measured flow field. Recent experimental measurements of the unsteady velocity field through the diffuser show that unsteadiness persists further into the diffuser passage than typically assumed [21], suggesting a strong influence of unsteady effects on the flow field. The methodology used for model selection herealways stepping towards a more physically realistic modelwas done to minimize the impact of omitted flow drivers.…”
Section: Frozen Rotor Resultsmentioning
confidence: 95%
“…The diffuser throat is located in this region and the flow is highly unsteady. Gooding et al [15] concluded that steady CFD computations do not accurately predict the flow in this region, specifically on the suction surface. The trailing edge pressure deviates by less than 1% on both the PS and SS which suggests the steady CFD appropriately predicts the static pressure rise in the diffuser.…”
Section: Instrumentationmentioning
confidence: 99%
“…CFD techniques are currently used for the design and flow analysis of turbomachinery, even with fully 3D stage configuration. Complete, fully 3D unsteady analysis can be performed to study the component coupling near surge conditions [26] or to simulate a complete surge cycle [27]. The same authors performed unsteady simulations at near surge conditions in centrifugal compressors with vaned diffusers [28].…”
Section: Introductionmentioning
confidence: 99%